Mucinous lesions of the appendix: a histopathological study - Oshan Shrestha; Reetu Baral (Journal of Pathology of Nepal)
Background: Mucinous lesions of the appendix are frequently misinterpreted in histopathological examination due to their relative rarity. Our study focuses on interpreting the histopathological spectrum of such lesions and understanding the disease burden of appendiceal mucinous lesions in a tertiary centre.